ANALISIS PENGARUH KARAKTERISTIK PEKERJAAN,KEPUASAN KERJA, MODAL PSIKOLOGI KARYAWAN TERHADAP KINERJA DENGAN MEDIASI ORGANIZATION CITIZENSHIP BEHAVIOR ( OCB ) ( STUDI DI PT BPRS ARTHA SURYA BAROKAH ) (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to determine and analyze the relationship between job characteristics, job satisfaction, employee psychological capital and OCB the performance of employees of BPRS Artha Surya Barokah ltd. samples that taken for this study are employees of BPRS Artha Surya Barokah ltd who have minimum term of 1 years, in job it is about 82 people. Samples were taken by using purposive sampling method. The research instrument was a questionnaire. The collected data was processed using a technique of multiple regression analysis with SPSS (Statistical Package for Social Science). The analysis showed 1) the characteristics of the work does not affect the OCB, 2) job satisfaction affect on OCB, 3) capital of the psychology of the employees do not influence OCB, 4) job characteristics affect the work positively, 5) job satisfaction does not affect the performance, job satisfaction does not affect the performance Keywords: job characteristics, job satisfaction, employee psychological capital, OCB, performance